Structural change and total factor productivity: Evidence from Germany - Philipp Henze (Kiel University, Department of Economics, 2015)
This paper uses a long time series of German employment data to test the theory of Ngai & Pissarides (2007). The theory suggests that the shift of employment shares from manufacturing to services is due to divergent growth rates of total factor productivity (TFP) in the two sectors. To test the theoretical predictions, I use the "Establishment History Panel" together with sectoral data on total factor productivity. The results confirm the theoretical predictions, i.e. they show a negative relationship between employment growth and TFP growth.
Keywords: L16; O14; O40; D24; 330; Structural Change; Economic Growth; Total Factor Productivity